Alternative energy - Schlager, Neil 1966-; Weisblatt, Jayne (Gale virtual reference library, 2006)
Introduces students to issues surrounding both current energy sources and alternative energy options. While there is significant discussion of the non-renewable resources now used to meet the majority of the world's energy needs (oil, coal and natural gas), the primary focus of the set is on newer options to meet the ever-growing demand.